Implementation of Chronic Disease Service Program (PROLANIS): Hypertension Disease in the Working Area of Tamansari Health Center, Tasikmalaya City - Aida Sri R; Sri Mulyanti; Heri Budiawan; Ana Anisa Y; Shinta K; Deden F (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Chronic disease is a type of disease that has a long duration of time. Chronic diseases, based on the 2013 Basic Health Research, are one of the main causes of death in Indonesia. The proportion of chronic diseases is quite large and requires enormous financing, namely 60% of the health financing of the entire community in Indonesia so that it needs special attention, which requires a breakthrough program that is preventive, promotive, curative, and rehabilitative on an ongoing basis, namely a health service system with effective and efficient service costs, namely PROLANIS. Puskesmas Tamansari Tasikmalaya City has 42 PROLANIS participants. This community service activity was carried out as an effort to assist partners, namely Puskesmas Tamansari, in implementing PROLANIS activities in the form of providing education about chronic diseases: hypertension, hypertension exercises and blood pressure checks which aim to make PROLANIS participants: hypertensive patients know their health status so that it is hoped that complications will not occur and quality of life can be optimal. The results of this community service were obtained by increasing knowledge and knowing the screening of disease risk factors for PROLANIS participants: hypertensive patients in the working area of the Tamansari Community Health Center, Tasikmalaya City.